2022
DOI: 10.1002/cl2.1239
|View full text |Cite
|
Sign up to set email alerts
|

Adult/child ratio and group size in early childhood education or care to promote the development of children aged 0–5 years: A systematic review

Abstract: Background: Worldwide, a large number of infants, toddlers, and preschoolers are enroled in formal non-parental early childhood education or care (ECEC).Theoretically, lower adult/child ratios (fewer children per adult) and smaller group sizes are hypothesised to be associated with positive child outcomes in ECEC. A lower adult/child ratio and a smaller group size may increase both the extent and quality of adult/child interactions during the day.Objectives: The objective of this review is to synthesise data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Although the meta-analysis study done by Dalgaard et al, (2022) 29 found a low relationship between the ratio of the number of teachers and students and effectiveness in teaching and learning. The 25 ratios shown in Sula Island and Taliabu Island were shocking.…”
Section: What Is the Ratio Of The Number Of Teachers And Students In ...mentioning
confidence: 95%
“…Although the meta-analysis study done by Dalgaard et al, (2022) 29 found a low relationship between the ratio of the number of teachers and students and effectiveness in teaching and learning. The 25 ratios shown in Sula Island and Taliabu Island were shocking.…”
Section: What Is the Ratio Of The Number Of Teachers And Students In ...mentioning
confidence: 95%
“…Educational quality in early childhood education is usually assessed in terms of criteria such as a high level of teacher education and adequate resourcing for centers, that includes low adult-child ratios and small group sizes (Vermeer et al, 2016). Low-ratio settings have been typically associated with better opportunities for children to interact with adults, though a recent meta-analysis suggests that their effects on children's developmental outcomes are the result of complex interactions between several variables, and that they might be compensated for larger ratio situations through, for instance, the teacher's professional competence (Dalgaard et al, 2022).…”
Section: Language Developmental Contexts and Early Childhood Educationmentioning
confidence: 99%
“…A national mechanism to ensure quality standards are upheld under the National Quality Framework (Australian Children's Education and Care Quality Authority, 2020) was established under the Education and Care Services National Law Act 2010 No. 69 of 2010 (2022) and is constituted of a key guiding framework document, the Early Years Learning Framework for Australia (EYLF) (Department of Education Employment and Workplace Relations, 2009) (a revised version of which was released in January 2023 and will be phased in over the course of 2023) and the implementation of the National Quality Standard (NQS) by the Regulator within each jurisdiction. There is little doubt of the commitment to quality ECEC both in terms of rhetoric and increasingly, funding.…”
Section: Conceptualizations Of Qualitymentioning
confidence: 99%
“…Whilst the NQS provides governments with valuable information about the ECEC system in an aggregated manner (Australian Children's Education and Care Quality Authority, 2022), it more importantly provides the basis for interventions where services are underperforming, increasingly forms the basis for differentiating ECEC services in a competitive market, and forms the basis of much of the effort to educate families about the importance of early education. Indeed, the NQF Annual Performance Report (2022) indicates that families' knowledge about the NQS is patchy; just 55% are aware of the quality rating system and less than two-thirds of those (who are aware) know the rating of the service they use. Understandably, and as reported in earlier research (Cloney et al, 2016), many families focus on pragmatic concerns (e.g., location, cost) when choosing a service.…”
Section: Conceptualizations Of Qualitymentioning
confidence: 99%